Controlling naphtha cracking using nanosized TON zeolite synthesized in the presence of polyoxyethylene surfactant - Jamil, A.K.; Muraza, O.; Sanhoob, M.; Tago, T.; Konno, H.; Nakasaka, Y.; Masuda, T. (Journal of analytical and applied pyrolysis, 2014)
•The nano-sized ZSM-22 crystals were applied in n-hexane cracking.•Nanocrystals showed better catalytic activity and selectivity to light olefins.•Effect of adding surfactant in ZSM-22 synthesis has been studied.•Polyoxyethylene (POE) with chain length equal 10 was used as a surfactant.•Effect of Si/Al in the presence of POE surfactant was studied. Valorization of naphtha, a derived intermediate from crude oil is still a crucial subject. Here we report an effort to control catalytic cracking of naphtha using nanosized TON zeolite, which was synthesized by microwave assisted hydrothermal synthesis (MAHyS) in the presence of polyoxyethylene-based surfactant. The effects polyoxyethylene (POE) surfactant on the crystal size, morphology and the crystal aspect-ratio were studied. The crystals with lengths in the range of 90–300nm were obtained. The addition of polyoxyethylene surfactant reduced the agglomeration rate of ZSM-22 zeolite crystals. The polyoxyethylene surfactant was added with POE/Al from 2.5 to 10. Effect of Si/Al in the presence of POE surfactant was studied by changing the Si/Al ratio from 45 to 80. Naphtha was simulated using a model compound, n-hexane. Excellent selectivity toward propylene was obtained over ZSM-22 zeolite crystals in n-hexane cracking. High selectivity to propylene was maintained over different size of ZSM-22 zeolite crystals. Decreasing crystal length from 300 to 90nm considerably increased the catalytic activity of ZSM-22 crystals.